Hexanal-induced changes in miRNA-mRNA interactions in A549 human alveolar epithelial cells - Cho, Y.; Lim, J.-H.; Jeong, S.-C.; Song, M.-K.; Ryu, J.-C. (Kluwer Academic Publishers, 2015)
Although hexanal is considered to be a major air pollutant the correlation between hexanal and health risk is largely unknown. Identifying aldehyde toxicity in eukaryotic cells will be useful for preventing and treating environmental diseases and disorders. However, it is important to note that previous microRNA (miRNA) studies of hexanal have not yet identified the functional relationship between miRNA and mRNA. The aim of this study is to investigate the modulation of the integrated miRNA-mRNA relationship following exposure to hexanal. A549 human alveolar epithelial cells were treated to a 20% inhibitory concentration (IC20) of hexanal for 48 h. The microarray analysis results showed that 6 miRNA were altered in the hexanal-exposed A549 cells. Integrated analysis of miRNA and mRNA expression profiles identified 445 miRNA-mRNA correlations. KEGG analysis of 445 putative target genes of hexanal-induced miRNAs indicated that 8 genes (ATP2B3, ATP2B4, CACNA1G, EDNRA, GRM5, ITPR2, ITPKB, PTGER3) are involved in the calcium signaling pathway, which plays an important role in Alzheimer’s and several inherited immunodeficiency diseases. Therefore, this study suggests the value of miRNA-mRNA networks in order to identify molecular regulation in response to hexanal exposure in an in vitro model. Furthermore, this approach provides insight into the potential biological process of toxicity and a better understanding of the toxicological mechanism of toxicants. ？ 2015, Korean Society of Environmental Risk Assessment and Health Science and Springer Science+Business Media Dordrecht.
Keywords: hexanal; messenger RNA; microRNA; air pollutant; Article; ATP2B3 gene; ATP2B4 gene; CACNA1G gene; calcium signaling; EDNRA gene; gene; gene control; gene expression; gene ontology; GRM5 gene; human; human cell; ITPKB gene; ITPR2 gene; microarray analysis; molecular genetics; priority journal; PTGER3 gene; Eukaryota